POLYCYTHEMIA VERA PRESENTING AS A PORTA HEPATIS MASS: A RARE PRESENTATION - Ahmed, Shanila; Irfan, Omar; Siddique, Sabeeh; Abid, Shahab (Journal of Ayub Medical College Abbottabad, 2019)
Polycythaemia Vera (PV) is a myeloproliferative disorder in which bone marrow has increased production of red blood cells, white blood cells and platelets. The hallmarks of the disease are veno-occlusive events, secondary to increased blood viscosity. Polycythaemia Vera rarely presents with portal vein thrombosis below age of 55 years especially in absence of any chronic liver disease. We report a case of 30-years-old South Asian male presenting with abdominal pain, weight loss and vomiting for 3 months. On evaluation, he was found to have oesophageal varices. Furthermore, CT scan showed infiltration at porta-hepatis and portal venous thrombosis. PV was diagnosed with a positive JAK2 mutation and increased haemoglobin. Laparoscopy was done to perform biopsy of the porta-hepatis mass. Biopsy showed engorged vessels with no sign of malignancy. Patient underwent repeated sessions of upper GI endoscopy for band ligation and multiple sessions of venous phlebotomy which drastically improved his blood indices. He was started on lifelong aspirin and was advised regular follow-ups. With early recognition and prompt management patients can be prevented from potential complications which can prove to be detrimental. Keywords: Polycythaemia Vera; Portal vein thrombosis; Varices; Splenomegaly